Enabling the Business of Agriculture 2015 : Progress Report - World Bank Group (Washington, DC, 2015)
Enabling the Business of Agriculture 2015 is a pilot assessment report on the agribusiness sector enabling environment in 10 countries. This progress report covers the methodology, key insights and lessons learned from the pilot effort. Enabling the Business of Agriculture 2015 is a first step toward identifying areas and data sets that can be used to build indicators in subsequent phases of the project; the indicators will measure and monitor policies and regulations that impact how markets function in the agricultural sector. The 10 countries represent a range of geographic regions in different stages of agricultural development, as follows: Ethiopia, Guatemala, Morocco, Mozambique, Nepal, the Philippines, Rwanda, Spain, Uganda, and Ukraine. Data are current as of 31 March, 2014. Enabling the Business of Agriculture breaks down the agricultural value chain the full range of activities and services needed to bring a commodity or product from production to sale in the final market into different topic areas. Six of these topics were selected for study during the pilot year registering agricultural land, accessing financial services, strengthening seed systems, improving fertilizer supply, transporting agricultural goods, and selling agricultural goods. Another three topics were chosen for initial testing: contracting agricultural production, electrifying rural areas, and connecting farmers to information.